Antarctic Bottom Water from the Adélie and George V Land coast, East Antarctica (140-149°E) - Guy Williams; Aoki, S; Jacobs, SS; Stephen Rintoul; Tamura, T; Nathaniel Bindoff (2010)
We report on observations of dense shelf water overflows and Antarctic Bottom Water (AABW) formation along the continental margin of the Adélie and George V Land coast between 140°E and 149°E. Vertical sections and bottom layer water mass properties sampled during two RVIB Nathaniel B Palmer hydrographic surveys (NBP00–08, December 2000/January 2001 and NBP04–08, October 2004) describe the spreading of cold, dense shelf water on the continental slope and rise from two independent source regions. The primary source region is the Adélie Depression, exporting high‐salinity dense shelf water through the Adélie Sill at 143°E. An additional eastern source region of lowersalinity dense shelf water from the Mertz Depression is identified for the first time from bottom layer properties northwest of the Mertz Sill and Mertz Bank (146°E–148°E) that extend as far as the Buffon Channel (144.75°E) in summer. Regional analysis of satellite‐derived ice production estimates over the entire region from 1992 to 2005 suggests that up to 40% of the total ice production for the region occurs over the Mertz Depression and therefore this area is likely to make a significant contribution to the total dense shelf water export. Concurrent time series from bottom‐mounted Microcats and ADCP instruments from the Mertz Polynya Experiment (April 1998 to May 1999) near the Adélie Sill and on the upper continental slope (1150 m) and lower continental rise (3250 m) to the north describe the seasonal variability in downslope events and their interaction with the ambient water masses. The critical density for shelf water to produce AABW is examined and found to be 27.85 kg m−3 from the Adélie Depression and as low as 27.80 kg m−3 from the Mertz Depression. This study suggests previous dense shelf water export estimates based on the flow through the Adélie Sill alone are conservative and that other regions around East Antarctica with similar ice production to the Mertz Depression could be contributing to the total AABW in the Australian‐Antarctic ...